2020
DOI: 10.1177/0963689720964384
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Clinical Safety of Human iPS Cell-Derived Liver Organoid Transplantation to Infantile Patients in Porcine Model

Abstract: Transplantation of liver organoids has been investigated as a treatment alternative to liver transplantation for chronic liver disease. Transportal approach can be considered as a method of delivering organoids to the liver. It is important to set the allowable organoid amount and verify translocation by intraportal transplantation. We first examined the transplantation tolerance and translocation of porcine fetal liver-derived allogeneic organoids using piglets. Fetal liver-derived organoids generated from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 35 publications
(43 reference statements)
0
27
0
Order By: Relevance
“…However, although liver transplantation is an effective treatment, patients have to take immunosuppressive drugs on a lifelong basis, and risk of rejection and need for dietary restrictions exist long after transplantation. While cell transplantation and gene therapy are being examined as novel treatments [ 5 , 8 , 9 , 10 ], their safety and therapeutic efficacies have not yet been determined. From this point of view, human disease models in which clinical equivalent treatments are executable are preferable for the development of novel medical technologies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, although liver transplantation is an effective treatment, patients have to take immunosuppressive drugs on a lifelong basis, and risk of rejection and need for dietary restrictions exist long after transplantation. While cell transplantation and gene therapy are being examined as novel treatments [ 5 , 8 , 9 , 10 ], their safety and therapeutic efficacies have not yet been determined. From this point of view, human disease models in which clinical equivalent treatments are executable are preferable for the development of novel medical technologies.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the severe fulminant OTCD model was established. The well-known OTCD model animals, sparse-fur (spf/1) mice (ID156, Balb/c background spontaneous mutation mice) show 1/6 the level of OTC activity (wild-type mice: 317.8 ± 51.5 nmol/min/mg, OTCD mice: 53.7 ± 33.5 nmol/min/mg, [mean ± SD, n = 3], unpublished data) and survive for approximately two months (median, 47 days; range: 20–52) [ 5 , 10 ]. In our previous study, hepatocyte transplantation two days after birth significantly prolonged the survival time in OTCD mice [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To note, the system described by Taniguchi’s group has achieved remarkable scalability (Takebe et al 2017 ) and also demonstrated the possibility to use different cell types derived from a single iPSC clone (Zhang et al 2018b ). This system has now been validated in larger porcine models for clinical safety with portal vein transplantation procedures and shows great promise for human clinical trials in the near future (Tsuchida et al 2020 ).…”
Section: Main Textmentioning
confidence: 99%
“…Moreover, the potential risks associated with genetic modification, tumorigenesis, and transplantation techniques should be emphasized in light of individual and societal values. In the context of continuing investigation regarding clinical concerns[ 79 , 80 ], quality-controlled and personalized LOs from authorized patient-derived cell banks are expected to be used routinely in the future.…”
Section: Current Challenges In Generating Multi-cellular Liver Organoidsmentioning
confidence: 99%